2019
DOI: 10.1002/jcb.28529
|View full text |Cite
|
Sign up to set email alerts
|

c‐Myc mediated upregulation of long noncoding RNA SNHG12 regulates proliferation and drug sensitivity in natural killer/T‐cell lymphoma

Abstract: Nasal-type natural killer/T-cell lymphoma (NKTCL) is an aggressive malignancy with poor outcomes. The treatment of NKTCL requires intensive chemotherapy.Long noncoding RNAs (lncRNAs) have been implicated in many cancers, including NKTCL. The elucidation of the multidrug resistance (MDR) may greatly contribute to explore novel therapeutic strategies. Herein, we explored the roles and potential regulatory mechanism of lncRNAs small nucleolar RNA host gene 12 (SNHG12) in MDR of NKTCL. We found that SNHG12 was upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 28 publications
(61 reference statements)
0
40
0
Order By: Relevance
“…4B). Interestingly, multiple small nucleolar RNA host genes were recently frequently reported in cancers (Damas et al, 2016;Dong et al, 2018;Guo et al, 2018;Jiang et al, 2018a;Shan et al, 2018;Sun et al, 2017;Xu et al, 2018;Zhu et al, 2019). In ESCC, we found that knockdown of SNHG10, an uncharacterized lncRNA, reduced proliferation, migration, and clonogenicity in KYSE150 and TE3 cells (Fig.…”
Section: Genome Instabilitymentioning
confidence: 68%
“…4B). Interestingly, multiple small nucleolar RNA host genes were recently frequently reported in cancers (Damas et al, 2016;Dong et al, 2018;Guo et al, 2018;Jiang et al, 2018a;Shan et al, 2018;Sun et al, 2017;Xu et al, 2018;Zhu et al, 2019). In ESCC, we found that knockdown of SNHG10, an uncharacterized lncRNA, reduced proliferation, migration, and clonogenicity in KYSE150 and TE3 cells (Fig.…”
Section: Genome Instabilitymentioning
confidence: 68%
“…Due to the heterogeneity of tumors and the complexity of the tumor microenvironment, these molecules can play a carcinogenic or tumor suppressive role in the same tumor. There is evidence that lncRNAs can act as molecular scaffolds, sponges or coactivators in tumor scaffolds by interacting with DNA, RNA or proteins [5,31,32] . At present, increasing evidence has shown that the abnormally high expression of SNHG12 plays a carcinogenic role in various malignant tumors [10][11][12][13][14][15][16][17][18][19][26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…Further research has shown that overexpression of SNHG12 is associated with rapid cancer proliferation, strong invasion and migration, and high rates of metastasis, recurrence, and chemical resistance [30][31][32] (Table 7). Moreover, in lung cancer, this molecule can inhibit metastasis and epithelial-mesenchymal transition when inhibited [12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of lncRNA GAS5 decreased miR-544 expression and increased RUNX3 expression, IFN-γ secretion and NK cell cytotoxicity [53]. It has been reported that lncRNA SNHG12 is a direct transcriptional target of c-Myc and that c-Myc-mediated upregulation of lncRNA SNHG12 expression promotes proliferation and inhibits sensitivity to cisplatin (CDDP) in natural killer/T-cell lymphoma [54]. In parallel, Ma and colleagues demonstrated that circRNA of AR-suppressed PABPC1 91 bp enhanced the cytotoxicity of natural killer cells against hepatocellular carcinoma.…”
Section: Natural Killer Cellsmentioning
confidence: 99%